Cancer Predictive Value of Exams preoperative in the thyroid nodule: part two: development of a predictive model - Cluzet, Oscar; Delgado, Bolívar; Yametti, Luis; Botta, Fernando (Cirugía del Uruguay, 1996)
Having previously identified in the analysis of 231 operated patients three risk factors which are significant for the prediction of finding of differentiated carcinoma of the thyroid: solitary nodule, rapid growth, and positive or suspicious puncture cytology, the authors were ab/e to determine the following data.